Stereoselective Total Synthesis of Paecilomycins E and F - Bhunia, Nisith; Das, Biswanath (Synthesis, 2015)
The stereoselective total synthesis of two bioactive resorcylic acid lactones, paecilomycins E and F has been accomplished thorough a general pathway using cis-butene-1,4-diol as the starting material. The pivotal steps of the synthesis include Sharpless asymmetric epoxidation, Bestmann–Ohira alkynation, Jacobsen kinetic resolution, and Heck coupling reaction.
Keywords: resorcylic acid lactones; paecilomycin E; paecilomycin F; total synthesis; cis-butene-1,4-diol